Is it Worth Starting Sexual Rehabilitation Before Radical Prostatectomy? Results From a Systematic Review of the Literature - Schoentgen, Nadja; Califano, Gianluigi; Manfredi, Celeste; Romero-Otero, Javier; Chun, Felix K. H.; Ouzaid, Idir; Hermieu, Jean-François; Xylinas, Evanguelos; Verze, Paolo (Frontiers in Surgery, 2021)
Background and purpose Sexual dysfunction (SD) is a frequent side effect associated with radical prostatectomy (RP) for prostate cancer (PCa). Some studies have showed the benefit associated with preoperative sexual rehabilitation (prehabilitation) and Enhanced Recovery After Surgery (ERAS) for RP but no clear clinical recommendations are yet available. Our aim was to conduct a systematic review on sexual prehabilitation prior to RP for patients with localized PCa and analyse the impact on postoperative sexual health compared with the standard post-operative care. Methods We performed a systematic review of the literature following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) recommendations. Results Four Randomized control trials and 1 retrospective comparative study were included in the analyses. Three of the 5 studies showed an improved EF recovery post-RP in the prehabilitation group compared to the standard of care represented by : higher International Index of Erectile Function 5 score (IIEF5) or IIEF score (p<0.0001) and a higher percentage of patient reporting return of EF based on the Sexual Encounter Profile (SEP) (56% vs. 24%, p = 0.007). Self-confidence, therapeutic alliance and adherence to treatment were stronger for patients with preoperative consultations (p<0.05) and EF recovery was better in case of higher number of follow-up visits (OR 4–5 visits versus 1 : 12.19, p = 0.002). Discussion Despite heterogenous methods and high risks of bias in this systematic review, starting sexual rehabilitation prior to surgery seems to ensure better EF recovery. This prehabilitation should include information of both patient and partner, with closer follow up and the use of a multimodal treatment approach that still remains to be defined and validated (oral medication, vacuum devices, pelvic floor muscle training etc.).